Comprehensive optimization design of low temperature insulation system of regeneration cryocooler. Issue 1 (1st May 2022) - Wang, Z K; Li, L F; Zhou, Y
Abstract: The calculation of radiant heat leakage is a part of the design of cryogenic insulation system. The numerical radiation simulation considering geometric structure of cryogenic insulation system is established through Monte Carlo method and view factor. The difference of the multi-layer insulation outer surface temperature is about 0.5% between the simulation and experimental results. Additionally, the structure and shape of the insulation system would make radiation to redistribute between surfaces. The surface would have less heat leakage with large aspect ratio and small radius.